Studies on Homalomeneae (Araceae) of Sumatera I: Homalomena hypsiantha, a distinctive new species of the Chamaecladon Supergroup - Boyce, P.C; Wong Sin, Yeng (Taylor & Francis Ltd., 2012)
A highly distinctive Homalomena new to science, Homalomena hypsiantha P.C.Boyce & S.Y.Wong sp. nov., is described from Sumatera. Inflorescence morphology assigns it to the Chamaecladon Supergroup of Homalomena, from all other described species of which is it distinguished by an exceptionally long-pedunculate inflorescence and a spathe inflating strongly at anthesis. A brief review of the status of Alderwerelt's species of Sumateran Chamaecladon Supergroup is offered. Homalomena hypsiantha is illustrated from living plants.